Acceptance of mobile payments by retailers using UTAUT model - Nor Hapiza Mohd Ariffin; Fauziah Ahmad; Umar Mohd Haneef (Institute of Advanced Engineering and Science, 2020)
Mobile payment is a form of payment transaction processing where the payer utilizes mobile communication methods together with mobile devices to initiate, authorize or complete payment. Hence, with the huge increase in mobile device usage, the retail sector will be able to collect large volumes of data. Unfortunately, most Malaysians still do not make full use of digital payments or cashless payments. Consumers in South East Asia still tend to use money or bank cards, and companies have been